Cost and Management Accounting. - Arora, M. N. (Himalaya Pub. House, 2009)
Management accounting is a fast growing and high value subject and all commerce and business graduates must possess knowledge of concepts, techniques and practices of this subject. It helps in planning and controlling of business operations and also in management decision making, which in turn assists in profit maximisation for the business. This book is an attempt to provide the students with through understanding or the management accounting concepts, methods and techniques. The subject matter has been presented in a systematic and intelligible manner with liberal use of numerical illustrations, charts and diagrams so as to make it interesting and sustain readers ̀interest. The book has been divided into nine chapters as per the curriculum of GGSIP University and UGC Model Curriculum. Based on the conviction that students can really learn management accounting by solving problems, the theory and problems approach has been adopted to fully meet all the examination needs of the students in this volume. Thus part from well organised theory, this book has sufficiently large number of solved problems and illustrations and unsolved problems with answers and hints, apart from objective type questions and selected theory questions. This will help students tackle examination questions with ease. The theory questions and practical problems and illustrations have been mostly selected from B.Com., BBA, CA, CS, ICWA and other examinations.